Legal Protection Against Consumers In Illegal Online Loans - Indah Aprilia Sidiki (Universitas Negeri Gorontalo, 2020)
INDAH APRILIA SIDIKI (NIM :1011418002 ) 2021. “LEGAL PROTECTION AGAINST CONSUMERS IN ILLEGAL ONLINE LOANS”. Supervised by each Supervisor I : Dr. Fence M. Wantu, SH., MH., and Supervisor II : Dolot Alhasni Bakung, SH., MH. Department of Law, Faculty of Law, State University of Gorontalo.This study discusses legal protection for consumers in illegal online loans. The purpose of this research is to find out legal protection for consumers in illegal online loans, and to find out the legal consequences of default in illegal online loans. The method used is normative research using library dataThe results of this study are that online loan service providers have been regulated in Financial Services Authority Regulation Number 77 /POJK.01/2016 concerning Information Technology-Based Borrowing-Lending Services, but not all online loan companies are registered with financial services authorities. Then the legal consequences of default in online loans are not clearly regulated because existing regulations only regulate defaults carried out by legal online loans, while illegal ones are only regulated for reprimands and up to blocking if proven guilty, related to consumers being transferred to the Criminal Code and the Protection Act. consumer.Keywords: Protection, loans, illegal